CryoSat: ESA's ice mission – Eight years in space. Issue 6 (15th September 2018) - Parrinello, T.; Shepherd, A.; Bouffard, J.; Badessi, S.; Casal, T.; Davidson, M.; Fornari, M.; Maestroni, E.; Scagliola, M.
Abstract: CryoSat-2 is a satellite of the European Space Agency that was launched in April 2010. It is intended to monitor changes in the thickness of the marine ice, floating in the polar oceans, and to measure variations in the thickness of the vast ice sheets that overlie Greenland and Antarctica. The CryoSat-2 satellite has replaced the original CryoSat, which became lost due to a launch failure in October 2005. CryoSat-2 carries an innovative radar altimeter called SIRAL (Synthetic Aperture Interferometric Altimeter). It has two radar antennas, which met the measurement requirements for ice-sheet elevation and sea-ice freeboard with unprecedented accuracy. The satellite orbits the planet at an altitude of around 720 km with a retrograde drifting orbit inclination of 92° and a "quasi" repeat cycle of 369 days (30 days sub-cycle). CryoSat-2 is therefore able to reach latitudes up to 88° covering more than 4.6 million km 2 of unexplored areas over the poles when compared with previous polar missions carrying an altimetry. The mission has achieved its prime objectives and is delivering high quality data, providing unique contributions to several Earth Science and applications domains, including ice, ocean, geodesy and hydrology, both at global and regional scales. The purpose of this paper is to provide a general overview of the mission and of its main scientific achievements after eight years in space.